1992
DOI: 10.1095/biolreprod46.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostanoids on the Rat’s Myometrium in Vitro during Pregnancy1

Abstract: The objectives of this study were to determine the effects of pregnancy in the rat on the contractile response of the myometrium in vitro to a number of prostanoids. Longitudinally and circularly oriented strips were studied separately. Responses to PG (prostaglandin)F2 alpha, PDG2, the PGI2-mimetic iloprost, and the thromboxane (Tx) A2-mimetic U-46619 were investigated on Days 10, 15, 18, 20, 21, and 22 of pregnancy. Responses were prostanoid-dependent, and differences between longitudinal and circular strips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…This pattern of FP receptor expression is similar to those previously reported for the myometrium [4,17] and entire uterus [2]. Responsiveness of the rat myometrium to PGF2α increases from Day 18 throughout the latter part of gestation [7]. Increases in FP receptor expression were reported to increase sensitivity of the myometrium to PGF2α action at term, even in the absence of increased PGF2α concentrations [4].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This pattern of FP receptor expression is similar to those previously reported for the myometrium [4,17] and entire uterus [2]. Responsiveness of the rat myometrium to PGF2α increases from Day 18 throughout the latter part of gestation [7]. Increases in FP receptor expression were reported to increase sensitivity of the myometrium to PGF2α action at term, even in the absence of increased PGF2α concentrations [4].…”
Section: Discussionsupporting
confidence: 85%
“…The PGs are recognized as the 'triggers' of labor [5] because the myometrium contracts in response to exogenous PGs both in vivo and in vitro [7,19], PG synthetic enzymes and levels in tissues and fluids increase before or at the time of labor, and inhibitors of PG synthesis delay birth and prolong pregnancy [15]. The current study clearly demonstrated that the FP receptor mRNA levels in rat uterus were low between Days 10 and 18 of gestation, significantly increased on Day 20, peaked during parturition, and fell rapidly after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…71 This evolution in the pattern of spontaneous con tractile activity with the initiation of labor is the manifestation of the transformation in the phenotype of the myometrium. With the approach of labor, the muscle demonstrates increased excitability (associated with a relative depolarization of the resting membrane potential, 67,72 it becomes highly respon sive to uterotonic agents 68,73,74 and the smooth muscle cells markedly increase their electrical coupling. 75 These changes act to increase the effectiveness of the uterotonic agents in generating high-frequency contractions and ensure that those contractions that are initiated rapidly spread to involve the entire uterus.…”
Section: Pattern Of Myometrial Activity Throughout Pregnancy and Partmentioning
confidence: 99%
“…Each receptor was coupled to a specific intracellular signaling system by G proteins, and FP and EP receptors appear to mediate uterine contractions either with or without utilization of the phospholipase pathway [11]. After incubation of rat longitudinal and circular myometrial strips with various prostanoid receptor agonists and antagonists to induce or inhibit a contractile response, Crankshaw and Gaspar [12] concluded that rat myometrium was not a target for PGI 2 or Tx but yielded a different pattern of response for PGE 2 and PGF 2 , suggesting that these PGs act at different sites in the myometrium.…”
Section: Introductionmentioning
confidence: 99%